STRATEGI PETANI DALAM MENINGKATKAN PRODUKTIVITAS PERTANIAN PADI DI DESA DIBAL KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Iemaaniah, Zuhdiyah Matienatul; Selvia, Siska Ita (JURNAL AGRIMANSION, 2023)
The area of agricultural land continues to decline due to land conversion. Agricultural land productivity is expected to continue to increase along with increasing population growth in a region. Increasing agricultural productivity is part of efforts to maintain local food security. This research aims to find out farmers' strategies in increasing the productivity of agricultural land which has experienced a decline in area, especially rice farming land. This research was conducted in Dibal Village, Ngemplak District, Boyolali Regency, which is a village affected by evictions from three public facilities. The research method uses descriptive qualitative with data collection through Focus Group Discussion (FGD) with stakeholders representing farmers in farmer groups and also the Dibal Village government. The research results showed that there are 6 strategies to increase rice productivity in Dibal Village, namely 1) There is high motivation in producing rice plants, 2) There is intensification of agricultural land, 3) There is an embroidery planting system by farmers, 4) The use of superior seeds, 5) The existence of solid farmer groups, 6) Availability of tools -agricultural equipment, 7) subsidies for fertilizer and agricultural medicines.